Indigenous Resilience and Indigenous Knowledge Systems in the context of Climate Change - Tsai, Huei-Min; Lin, Yih-Ren; Bayrak, Mucahid Mustafa (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Indigenous peoples, in Taiwan and worldwide, need to come up with various ways to cope with and adapt to rapid environmental change. This edited book, which is a follow-up to a conference entitled "Climate Change, Indigenous Resilience and Local Knowledge Systems: Cross-time and Cross-boundary Perspectives" organized by the Research Institute for the Humanities and Social Sciences, Ministry of Science and Technology, presents 16 papers which explore the various dimensions of Indigenous resilience to climate change and disasters in Taiwan and other regions in the world. This book explores the interrelated themes of climate change and Indigenous knowledge-based responses, and Indigenous (community) resilience with specific reference to Typhoon Morakot and beyond. The goals of this book are to discuss the international experience with Indigenous resilience; to review Indigenous knowledge for adaptation to climate change and disasters; and to generate a conversation among scholars, Indigenous peoples, and policy-makers to move the agenda forward. This book focusses on Indigenous resilience, the ways in which cultural factors such as knowledge and learning, along with the broader political ecology, determine how local and Indigenous people understand, deal with, and adapt to environmental change.